A methoxysilane-porphyrin polymer modified ceramic composite, a separator and applications thereof

CN122889953APending Publication Date: 2026-10-09GUANGDONG SAFIAN NEW MATERIAL CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610982984.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-02
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而聚烯烃材料存在固有的缺陷:聚烯烃隔膜的表面能较低、亲水性差会导致电解液浸润性不佳,锂离子传输阻力变大,影响电池的倍率性能和循环寿命;聚烯烃的热稳定性有限,当电池内部温度过高时,隔膜容易熔化甚至破裂,导致正负极直接接触,造成安全隐患;聚烯烃隔膜的力学性能和电化学腐蚀性有待提升,难以满足高能量密度、高安全锂离子电池发展需求

Benefits of technology

[0032]本发明在已经研究的基础上,研究了卟啉自聚物直接和氧化铝结合后的性能,经过实验,发现相比已有研究在耐热稳定性、可分散性、强度、柔韧性进一步提高;

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a methoxysilane-porphyrin polymer modified ceramic composite, which comprises nanoscale alumina microspheres and methoxysilane-porphyrin polymers loaded on the nanoscale alumina microspheres; the methoxysilane-porphyrin polymer is a porphyrin self-polymer grafted with methoxysilane groups. The composite couples alumina through methoxysilane and connects the porphyrin polymer through a covalent bond, so that the alumina and the separator can simultaneously satisfy the strength and flexibility based on the inherent properties of the porphyrin polymer; in addition, the optimization of the ion conduction path is also a feature of the product, in traditional products, the correlation between the ion conduction path constructed by the porphyrin polymer and the physical pores between the ceramic particles is not strong, in the application, the transmission network of physical + chemical channels is formed by being loaded on the alumina, the impedance of ion migration is reduced, and the ion conductivity is improved; in addition, the heat resistance, dispersibility and other performances are also significantly improved. Another purpose of the application is to provide the application of the composite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of new energy, specifically to a methoxysilane-porphyrin polymer-modified ceramic composite, a membrane, and its applications. Background Technology

[0002] Currently, commercial lithium-ion batteries generally use single-layer polyolefin (PE / PP) microporous polymer membranes due to their excellent pore structure, high mechanical strength, and electrochemical stability. However, polyolefin materials have inherent defects: the low surface energy and poor hydrophilicity of polyolefin membranes lead to poor electrolyte wettability, increasing lithium-ion transport resistance and affecting the battery's rate performance and cycle life; polyolefins have limited thermal stability, and when the internal temperature of the battery is too high, the membrane is prone to melting or even rupture, resulting in direct contact between the positive and negative electrodes and creating safety hazards; the mechanical properties and electrochemical corrosion resistance of polyolefin membranes need to be improved, making it difficult to meet the development requirements of high-energy-density and high-safety lithium-ion batteries.

[0003] To address these issues, researchers have explored various modification methods, including surface coating, blending modification, and chemical grafting. Currently, a commonly used approach is to modify polyolefin membranes using ceramic coating technology. By constructing a ceramic coating on the surface of the polyolefin membrane, its high-temperature resistance and electrolyte affinity can be effectively improved, thereby reducing the risk of thermal shrinkage and improving ion transport efficiency.

[0004] For example, in the prior art, Chinese patent application 201620045629.2 discloses a soft ceramic lithium-ion battery separator, which includes a polyolefin microporous membrane base layer, wherein the upper and / or lower surfaces of the polyolefin microporous membrane base layer are covered with a soft ceramic layer, wherein the soft ceramic layer is a boehmite particle layer.

[0005] The aforementioned prior art 1 uses ceramic coating technology to modify polyolefin membranes. However, current ceramic modification technology still has shortcomings: poor interfacial compatibility between ceramic particles and polyolefin matrix leads to easy peeling of the coating layer, affecting the integrity of the membrane and its long-term cycle life.

[0006] Prior art 2: Patent application CN121906085A, entitled "A polyethylene diaphragm co-coated with porphyrin self-polymer and ceramic material, its preparation method, and its application," uses a 5,10,15,20-tetra(4-methoxycarbonylphenyl)porphyrin polymer as the bonding layer between the ceramic coating and the polyethylene film. Its main mechanism is that in the methoxycarbonylphenyl porphyrin self-polymer, the polar methoxycarbonyl group can form dipole-dipole interactions and hydrogen bonds with neighboring molecules, increasing the bonding force between molecular chains and reducing deformation caused by local stress concentration. Simultaneously, the rigid planar structure of the porphyrin macrocycle forms a tightly ordered layered arrangement through π-π stacking, restricting the free rotation and vibration of the molecular chains, reducing the damage to the material structure caused by thermal motion, and combined with the ceramic layer as a rigid skeleton, achieving multi-level synergistic support, significantly improving the thermal stability and mechanical strength of the diaphragm.

[0007] The above methods have sufficient strength but insufficient flexibility, and there is room for improvement in reducing impedance and other aspects.

[0008] The present invention is proposed in light of the aforementioned difficulties. Summary of the Invention

[0009] One objective of this invention is to provide a methoxysilane-porphyrin polymer-modified ceramic composite. This composite couples alumina with methoxysilane and covalently links the porphyrin polymer, enabling the alumina and the membrane to achieve both strength and flexibility based on the inherent properties of the porphyrin polymer. Furthermore, the optimized ion transport pathway is another feature of this product. In traditional products, the correlation between the ion transport pathway constructed by the porphyrin polymer and the physical channels between ceramic particles is not strong. In this invention, by loading the porphyrin polymer onto alumina, a transport network of physical and chemical channels is formed, reducing the impedance of ion migration and improving ion conductivity. In addition, properties such as thermal stability and dispersibility are also significantly improved.

[0010] Another object of the present invention is to provide the application of the complex.

[0011] To achieve the above objectives, the present invention provides a methoxysilane-porphyrin polymer-modified ceramic composite, comprising nano-sized alumina microspheres and porphyrin self-polymers supported on the nano-sized alumina microspheres; wherein the porphyrin self-polymers are grafted with methoxysilane groups.

[0012] CN121906085A verified the use of 5,10,15,20-tetraphenylporphyrin monomers to self-polymerize on the base membrane to achieve the bonding between the base membrane and the ceramic layer. In this scheme, the binding force of the self-polymer and the rigid planar structure of the porphyrin macrocycle are utilized to form a tight and orderly layered arrangement through π-π stacking to reduce motion damage and thus improve the membrane performance.

[0013] In this invention, further research and development are carried out based on this technology;

[0014] In this invention, the three-layer structure in the original technology is optimized into a two-layer structure by grafting silane onto the self-polymer, coupling alumina through silane, and improving the bonding effect with the substrate through the self-polymer; ultimately achieving a comprehensive improvement in flexibility, strength, and heat resistance stability.

[0015] The most important aspect of this invention is that, through the above optimization, the ion conduction path can be effectively improved, the impedance of ion migration can be reduced, and the ion conductivity can be increased.

[0016] The underlying logic is as follows: Tetraphenylporphyrin has a large π-conjugated structure, and the polar nitrogen atom at the center of its pyrrole ring can act as a Lewis base site, coordinating with metal ions in the electrolyte, which can significantly accelerate ion migration at the interface; the conjugated plane of tetraphenylporphyrin interacts with lithium ions, which can construct low-energy ion conduction pathways within the coating, complementing the physical channels between ceramic particles to form a transport network of physical + chemical channels, reducing the impedance of ion migration and improving ion conductivity; tetraphenylporphyrin enhances its high surface energy binding with ceramic particles by grafting methoxysilyl groups, exhibiting strong hydrophilicity and achieving rapid and uniform wetting.

[0017] In some preferred embodiments of the present invention, the porphyrin molecules constituting the porphyrin self-polymer are one or more combinations of 5,10,15,20-tetraphenylporphyrin, 5,10,15,20-tetra(4-methoxycarbonylphenyl)porphyrin, and 5,10,15,20-tetra(4-aminophenyl)porphyrin.

[0018] After verification, we found that the three substances mentioned above each have their own advantages. Among them, 5,10,15,20-tetra(4-methoxycarbonylphenyl)porphyrin has methoxycarbonyl groups attached to all four benzene rings, which can form conjugated carbonyl groups, optimize coordination with metal ions in the electrolyte, and significantly accelerate ion migration at the interface. At the same time, after 5,10,15,20-tetra(4-methoxycarbonylphenyl)porphyrin is grafted with methoxysilane, it can synergistically reduce the impedance of ion migration and improve ionic conductivity.

[0019] The side chain amino groups of 5,10,15,20-tetra(4-aminophenyl)porphyrin can directly form hydrogen bonds and coordinate with hydroxyl groups and Lewis acid sites on the surface of alumina, thereby improving the binding stability with alumina. Combined with the synergistic effect of methoxysilyl groups, it can significantly improve the flexibility of the membrane.

[0020] In the above-mentioned ceramic composite, the method for preparing the porphyrin self-polymer is as follows:

[0021] Step 1: Porphyrin molecules are polymerized in the first solvent system in the presence of a catalyst to obtain porphyrin self-polymers;

[0022] Step 2: The porphyrin self-polymer and the monomer containing the methoxysilyl group are reacted in the second solvent system in the presence of an initiator to obtain the methoxysilane-porphyrin polymer.

[0023] In the above-mentioned ceramic composite, the catalyst is a Lewis acid; the weight ratio of the catalyst to the porphyrin molecule is 0.3~0.6:1; the initiator is an oil-soluble initiator, and the initiator is equivalent to 0.5~1.5 wt% of the porphyrin polymer.

[0024] The reaction temperature in step 1 is 70~90℃; the reaction temperature in step 2 is 70~90℃;

[0025] The first solvent system and the second solvent system are each independently 1,2-dichloroethane and toluene.

[0026] In the above-mentioned ceramic composite, the weight ratio of the porphyrin molecule, the monomer containing the methoxysilyl group, and the nano-sized alumina microspheres is 1:5~15:1~5.

[0027] In the above-mentioned ceramic composite, the D50 particle size of the nano-sized alumina microspheres is ≤100nm.

[0028] Meanwhile, the present invention also discloses a diaphragm, comprising a base membrane and a ceramic coating; the ceramic material used for the ceramic coating is as shown in any of the above descriptions.

[0029] In the above-mentioned diaphragm, the diaphragm is made of polyethylene; the thickness of the ceramic coating is (1)~(5) μm.

[0030] Finally, the present invention also discloses the use of the separator described above in the preparation of lithium-ion batteries or sodium-ion batteries.

[0031] Beneficial effects

[0032] Based on previous research, this invention investigated the properties of porphyrin self-polymers directly combined with alumina. Through experiments, it was found that compared with existing research, the heat resistance, dispersibility, strength, and flexibility were further improved.

[0033] More importantly, by using the composite method of the present invention, the transport network of physical + chemical channels formed by the ion conduction path is optimized, the impedance of ion migration is reduced, and the ion conductivity is improved; in addition, there is also a significant improvement in wetting performance. Detailed Implementation

[0034] The present invention will be further described below with reference to embodiments, but this does not constitute any limitation on the present invention. Any limited modifications made within the scope of the claims of the present invention are still within the scope of the claims of the present invention.

[0035] To illustrate the technical content of the present invention in detail, the following description is provided in conjunction with the embodiments.

[0036] Example 1: The mass ratio of Al2O3 to methoxysilane-porphyrin polymer was 1:1.

[0037] Step 1: Under nitrogen atmosphere, add 1 g of TPP (5,10,15,20-tetraphenylporphyrin) to 20 mL of 1,2-dichloroethane. Stir at room temperature for 30 min to ensure complete dissolution, yielding a clear purple liquid. Add 0.5 g of catalyst AlCl3 and react for 30 min to ensure thorough mixing. Then, slowly raise the temperature to 80 °C and stir at this temperature for 24 h. After the reaction is complete, cool to room temperature, filter, and wash with methanol and dichloromethane until the solution is clear. Dry the resulting solid to obtain the tetraphenylporphyrin self-polymer TPP-HCP.

[0038] Step 2: Preparation of methoxysilane-porphyrin polymer

[0039] TPP-HCP was added to a mixed solution of 10 mL MPTS (3-(methacryloyloxy)propyltrimethoxysilane), 1 wt% (with MPTS as 100 wt%) AIBN (azobisisobutyronitrile), and toluene, and reacted at 80 °C for 12 h. After the reaction was completed, the mixture was cooled to room temperature, washed repeatedly with toluene and ethanol, and dried to obtain the methoxysilane-tetraphenylporphyrin polymer MPTS-TPP.

[0040] Step 3: Preparation of polymer by modifying ceramics with methoxysilane-porphyrin polymer

[0041] 1g of ceramic Al2O3 was ball-milled into powder (D50 < 100nm) and added to a mixture of ethanol / acetic acid / deionized water (volume ratio 90:4:6). The powder was then ultrasonicated for 30 min to ensure uniform dispersion. 0.5g of MPTS-TPP was added to the mixture, and the mixture was stirred at room temperature for 24 h. After the reaction was complete, the mixture was dried to obtain the methoxysilane-porphyrin polymer-modified ceramic polymer Al2O3-MPTS-TPP.

[0042] Step 4: Preparation of the coated diaphragm

[0043] Base film pretreatment: Take a polyethylene base film (thickness 7μm, porosity 35%), cut it to 100mm×100mm, place it in a 1:1 volume ratio of ethanol and water mixed solution, and place it in an ultrasonic instrument for 30min to remove dust and contaminants from the surface of the base film; after ultrasonic treatment, take the base film out with tweezers and place it in a vacuum drying oven at 80℃ to dry it until the moisture is completely evaporated.

[0044] Preparation of coating solution: Take 1g of polymer Al2O3-MPTS-TPP powder, grind the powder to an average particle size of about 100nm using a ball mill, add it to 100mL of deionized water, add 0.01g of polyvinylidene fluoride, and ultrasonically disperse the mixed solution to form a dispersed coating slurry; fix the polyethylene coating diaphragm on the coating machine, and coat the Al2O3-MPTS-TPP slurry onto the surface of the base film.

[0045] Drying and curing: After coating, the obtained composite film is placed in a vacuum drying oven, the temperature is raised to 80℃, and dried and cured for 12 hours to remove residual solvent, thus obtaining a "Al2O3-MPTS-TPP+polyethylene" double-layer coated diaphragm.

[0046] The thickness of Al2O3-MPTS-TPP is 2.5 μm.

[0047] Example 2: The mass ratio of Al2O3 to methoxysilane-porphyrin polymer was 2:1.

[0048] The operation steps are exactly the same as in Example 1; the difference is that the mass of Al2O3 powder is adjusted to 2g, and the other parameters (temperature, time, coating rate) are kept the same as in Example 1.

[0049] Example 3: The mass ratio of Al2O3 to methoxysilane-porphyrin polymer was 3:1.

[0050] The operation steps are exactly the same as in Example 1; the difference is that the mass of Al2O3 powder is adjusted to 3g, and the other parameters (temperature, time, coating rate) are kept the same as in Example 1.

[0051] Example 4: The mass ratio of Al2O3 to methoxysilane-porphyrin polymer was 4:1.

[0052] The operation steps are exactly the same as in Example 1; the difference is that the mass of Al2O3 powder is adjusted to 4g, and the other parameters (temperature, time, coating rate) are kept the same as in Example 1.

[0053] Example 5: The mass-to-volume ratio of TPP and MPTS was adjusted to 1:5.

[0054] The operating steps are exactly the same as in Example 1; the difference is that the MPTS is adjusted to 5 ml, and the other parameters (temperature, time, coating rate) are kept the same as in Example 1.

[0055] Example 6: The mass-to-volume ratio of TPP and MPTS was adjusted to 1:15.

[0056] The operating steps are exactly the same as in Example 1; the difference is that the MPTS is adjusted to 15ml, and the other parameters (temperature, time, coating rate) are kept the same as in Example 1.

[0057] Example 7: Adjustment of process parameters

[0058] The operation steps are exactly the same as in Example 1; the difference is that the amount of catalyst used is 0.3g; the amount of initiator used is 0.5wt%; the reaction temperature in step 1 is 70℃, and the reaction temperature in step 2 is 70℃.

[0059] Example 8: Adjustment of process parameters

[0060] The operation steps are exactly the same as in Example 1; the difference is that the amount of catalyst used is 0.6g; the amount of initiator used is 1.5wt%; the reaction temperature in step 1 is 90℃, and the reaction temperature in step 2 is 90℃.

[0061] Example 9: Selection of Porphyrin Molecules

[0062] The general formula is the same as in Example 1, except that 5,10,15,20-tetra(4-methoxycarbonylphenyl)porphyrin is used instead of 5,10,15,20-tetraphenylporphyrin.

[0063] Example 10: Selection of Porphyrin Molecules

[0064] The general formula is the same as in Example 1, except that 5,10,15,20-tetra(4-aminophenyl)porphyrin is used instead of 5,10,15,20-tetraphenylporphyrin.

[0065] Example 11: Selection of Porphyrin Molecules

[0066] The results are largely the same as in Example 2, except that 5,10,15,20-tetra(4-aminophenyl)porphyrin is used instead of 5,10,15,20-tetraphenylporphyrin.

[0067] Example 12: Selection of Porphyrin Molecules

[0068] The results are largely the same as in Example 3, except that 5,10,15,20-tetra(4-aminophenyl)porphyrin is used instead of 5,10,15,20-tetraphenylporphyrin.

[0069] Example 13: Selection of Porphyrin Molecules

[0070] It is largely the same as Example 5, except that 5,10,15,20-tetra(4-aminophenyl)porphyrin is used instead of 5,10,15,20-tetraphenylporphyrin.

[0071] Example 14: Selection of Porphyrin Molecules

[0072] It is largely the same as Example 6, except that 5,10,15,20-tetra(4-aminophenyl)porphyrin is used instead of 5,10,15,20-tetraphenylporphyrin.

[0073] Comparative Example 1:

[0074] Refer to the applicant's prior application CN121906085A, a polyethylene diaphragm co-coated with porphyrin molecular self-polymer and ceramic material, its preparation method, and Example 1 of its application.

[0075] The specific preparation method is as follows:

[0076] Step 1: Take a polyethylene film (7μm thick, 35% porosity), cut it to 100mm×100mm, place it in a 1:1 mixture of ethanol and deionized water, ultrasonically clean it for 30min, and then place it in a vacuum drying oven at 80℃ until all the moisture evaporates to obtain a pretreated polyethylene film.

[0077] Step 2: Add 1g of 5,10,15,20-tetratetra(4-methoxycarbonylphenyl)porphyrin monomer powder to a flask containing 10mL of anhydrous 1,2-dichloroethane. After dissolving, add 0.3g of dimethoxymethane and 0.5g of anhydrous AlCl3 and mix well to obtain a methoxycarbonylphenylporphyrin coating solution.

[0078] Step 3: The methoxycarbonylphenyl porphyrin coating solution is uniformly coated onto the pretreated polyethylene film. After coating, the film is transferred to a vacuum environment at 75°C and kept at that temperature for 24 hours for crosslinking. The thickness of the 5,10,15,20-tetra(4-methoxycarbonylphenyl)porphyrin polymer layer is 1 μm.

[0079] Step 4: Take 1g of Al2O3 powder (D50<100nm), add it to 100mL of deionized water, then add 0.01g of ammonium polyacrylate and 0.01g of polyvinylidene fluoride, and disperse evenly to obtain Al2O3 ceramic slurry.

[0080] Step 5: Coat the Al2O3 ceramic slurry onto the 5,10,15,20-tetra(4-methoxycarbonylphenyl)porphyrin polymer layer, and place it in a vacuum drying oven. Raise the temperature to 70°C and dry and cure for 26 hours to obtain a polyethylene membrane co-coated with porphyrin self-polymer and ceramic material; wherein the thickness of the Al2O3 ceramic layer is 2μm.

[0081] Performance testing

[0082] 1. Surface density: Measure the mass and area of ​​the diaphragm using an analytical balance. Surface mass = mass / area. Test at least 5 points to estimate the uniformity of the surface mass.

[0083] 2. Air permeability: Gurley air permeability meter. Characterizes the porosity of the membrane and the electrolyte wetting rate; the lower the test value, the better the air permeability of the membrane.

[0084] 3. Mechanical properties:

[0085] Tensile strength: A stretching machine cuts the diaphragm into strips, sets the distance and stretching speed, and stretches it until it breaks. Tensile strength = maximum tensile force / (width × thickness).

[0086] Puncture strength: A tensile tester equipped with a puncture probe was used to record the maximum force with which the probe punctured the diaphragm.

[0087] Peel strength: Fix the sample on the platen of the stretching machine, tightly adhere it to the coating surface with standard tape, clamp the free end of the tape, peel it upwards, and record the result.

[0088] 4. Thermal properties:

[0089] Heat shrinkage rate: Remove the diaphragm sample, place it in an oven at a set temperature for 60 minutes, remove the sample, and measure the dimensional change after cooling. Heat shrinkage rate = [(original length - shrinkage length) / original length] × 100%.

[0090] 5. Electrical properties:

[0091] For the test of membrane conductivity, the reference method is: GB / T 36363-2018, Polyolefin Separators for Lithium-ion Batteries; Section 6.6: Electrical Properties - Ionic Conductivity.

[0092] The test results are shown in Table 1.

[0093] Table 1 Test Results

[0094] <![CDATA[Areal density (g / m 2 )]]> Breathability (s / ml) <![CDATA[Tensile strength (Kgf / cm 2 )]]> Puncture strength (gf) Peel strength (N / m) Heat shrinkage rate (%) Ionic conductivity (mS / cm) Example 1 7.95 168 1960 553.5 145 1.6 0.91 Example 2 8.03 172 1941 550.2 142 1.7 0.92 Example 3 8.11 177 1945 558.3 143 1.5 0.89 Example 4 8.18 182 1937 559.2 140 1.9 0.87 Example 5 8.02 173 1930 550.4 138 2.1 0.88 Example 6 8.05 170 1932 550.8 140 2.0 0.87 Example 7 8.08 177 1957 550.2 142 1.9 0.90 Example 8 7.99 173 1949 549.7 144 1.8 0.88 Example 9 8.01 173 1963 550.3 148 2.0 0.94 Example 10 7.99 165 1993 567.5 149 1.6 0.92 Example 11 8.03 172 1985 565.4 148 1.8 0.92 Example 12 8.01 175 1988 567.8 145 1.7 0.90 Example 13 8.08 179 1981 562.6 140 1.6 0.87 Example 14 8.12 183 1985 564.5 142 1.7 0.89 Comparative Example 1 8.02 175 1840 522.56 130 2.3 0.77

[0095] Results analysis:

[0096] 1. As can be seen from Examples 1 to 4, with the increase of alumina, the areal density and air permeability both increase, while having little effect on other non-electrical properties; the ionic conductivity decreases; as can be seen from Examples 1, 5 and 6, the optimal amount of organosilicon is 10 ml.

[0097] 2. As can be seen from Examples 1, 9, 10 to 14, the application performance of 5,10,15,20-tetra(4-methoxycarbonylphenyl) and 5,10,15,20-tetra(4-aminophenyl) is significantly better than that of 5,10,15,20-tetraphenylporphyrin, especially in terms of heat shrinkage and ionic conductivity. As can be seen from Examples 10 to 14, compared with Examples 1-3, 5 and 6, their mechanical strength is significantly better than that of the comparable cases, especially in terms of tensile strength (an important indicator of flexibility) and puncture strength.

[0098] 3. All embodiments of the present invention are superior to the comparative examples, proving that the optimization of the present invention is successful and has strong application value.

[0099] The embodiments presented herein are merely selected implementations based on combinations of all possible embodiments. The appended claims should not be limited to the embodiments described herein. Some numerical ranges used in the claims include sub-ranges within them, and variations within these ranges should also be covered by the appended claims.

Claims

1. A methoxysilane-porphyrin polymer-modified ceramic composite, characterized in that, It includes nanoscale alumina microspheres and a methoxysilane-porphyrin polymer supported on the nanoscale alumina microspheres; the methoxysilane-porphyrin polymer is a porphyrin self-polymer.

2. The ceramic composite according to claim 1, characterized in that, The porphyrin molecules constituting the porphyrin self-polymers are one or more combinations of 5,10,15,20-tetraphenylporphyrin, 5,10,15,20-tetra(4-methoxycarbonylphenyl)porphyrin, and 5,10,15,20-tetra(4-aminophenyl)porphyrin.

3. The ceramic composite according to claim 2, characterized in that, The preparation method of the methoxysilane-porphyrin polymer is as follows: Step 1: Porphyrin molecules are polymerized in the first solvent system in the presence of a catalyst to obtain porphyrin self-polymers; Step 2: The porphyrin self-polymer and the monomer containing the methoxysilyl group are reacted in the second solvent system in the presence of an initiator to obtain the methoxysilane-porphyrin polymer.

4. The ceramic composite according to claim 3, characterized in that, The catalyst is a Lewis acid; the weight ratio of the catalyst to the porphyrin molecule is 0.3~0.6:1; the initiator is an oil-soluble initiator, and the initiator is equivalent to 0.5~1.5 wt% of the porphyrin polymer. The reaction temperature in step 1 is 70~90℃; the reaction temperature in step 2 is 70~90℃; The first solvent system and the second solvent system are each independently 1,2-dichloroethane and toluene.

5. The ceramic composite according to claim 3, characterized in that, The weight ratio of the porphyrin molecule, the monomer containing the methoxysilyl group, and the nano-sized alumina microspheres is 1:5~15:1~5.

6. The ceramic composite according to claim 1, characterized in that, The D50 particle size of the nano-sized alumina microspheres is ≤100nm.

7. A diaphragm, characterized in that, It includes a base film and a ceramic coating; the ceramic material used for the ceramic coating is as described in any one of claims 1 to 6.

8. The diaphragm with a diameter of 7 μm according to claim 8, characterized in that, The diaphragm is made of polyethylene; the ceramic coating has a thickness of 1~5μm.

9. Use of the separator as described in claim 7 or 8 in the preparation of lithium-ion batteries or sodium-ion batteries.

Citation Information

Patent Citations

  • Polyethylene diaphragm jointly coated with porphyrin molecule autopolymer and ceramic material as well as preparation method and application of polyethylene diaphragm

    CN121906085A

  • Soft ceramic lithium ion battery diaphragm

    CN205406613U